2020
DOI: 10.2106/jbjs.20.00257
|View full text |Cite
|
Sign up to set email alerts
|

Determining Diagnostic Thresholds for Acute Postoperative Periprosthetic Joint Infection

Abstract: Background: The diagnosis of periprosthetic joint infection (PJI) in the early postoperative period remains a challenge. Although studies have established that serum C-reactive protein (CRP) and synovial markers may be useful, recent studies have suggested that the current thresholds used may lack sensitivity. The purpose of this study was to examine the role of serum CRP, erythrocyte sedimentation rate (ESR), synovial fluid white blood-cell (WBC) count, and polymorphonuclear neutrophil (PMN) perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 10 publications
1
32
0
1
Order By: Relevance
“…This suggests that the circulatory system CRP is detected by spreading to the synovial fluid through increased vascular and synovial permeability due to infection [14,19]. We determined that the serum CRP threshold for diagnosing chronic PJI was 10 mg/l, which was significantly lower than the results (39.8 mg/l) of a recent multicentric study conducted by Parvizi [20]. We found that when the threshold of synovial CRP was 7.26 mg/l, the AUC area of chronic PJI was as high as 93.70% (95%CI 0.869 to 0.976).…”
Section: Discussionmentioning
confidence: 72%
“…This suggests that the circulatory system CRP is detected by spreading to the synovial fluid through increased vascular and synovial permeability due to infection [14,19]. We determined that the serum CRP threshold for diagnosing chronic PJI was 10 mg/l, which was significantly lower than the results (39.8 mg/l) of a recent multicentric study conducted by Parvizi [20]. We found that when the threshold of synovial CRP was 7.26 mg/l, the AUC area of chronic PJI was as high as 93.70% (95%CI 0.869 to 0.976).…”
Section: Discussionmentioning
confidence: 72%
“…This suggests that the circulatory system CRP is detected by spreading to the synovial uid through increased vascular and synovial permeability due to infection [13,19]. We determined that the serum CRP threshold for diagnosing chronic PJI was 10mg/l, which was signi cantly lower than the results (39.8 mg/l) of a recent multicentric study conducted by Parvizi [20]. We found that when the threshold of synovial CRP was 7.26 mg/l, the AUC area of chronic PJI was as high as 93.70% (95 CI 0.869 to 0.976).…”
Section: Discussionmentioning
confidence: 73%
“…As the thresholds for diagnosing low-grade PJI are neither validated for the post-operative period nor dislocations or implant breakage, we applied thresholds according to Sukhonthamarn et al that we thought to be the most suitable. The authors investigated thresholds for PJI and their time-dependent change within 90 days of the index arthroplasty [ 7 ]. Regardless of the clinical diagnosis, the cases were defined as septic or aseptic using this modified version of the EBJIS classification of PJI.…”
Section: Methodsmentioning
confidence: 99%
“…It appears that common synovial biomarkers like WBC are elevated, but not specific for PJI diagnostics after THA dislocations [ 10 ]. In the presence of aseptic local inflammation, the diagnostic value of conventional synovial and serum markers may therefore be impaired and low-grade PJI may be likely overlooked [ 6 , 7 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%